(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The aim of the study was to determine the extent to which the management of high Involvement affects the dimensions of decision-making, information acquisition, revenue sharing, and knowledge ownership in the self-efficacy variable of human resources. The study was applied in a sample of Iraqi faculties (217) . The researchers reached a number of conclusions, the most important of which is that it is possible to benefit from the mechanisms and the dimensions of the management of high containment in the development of the self-efficacy of human resources. The main recommendations of the study were the need to give faculty members the necessary authority to perform their work properly,Teaching.